2000
DOI: 10.1111/j.1574-6968.2000.tb09215.x
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringensepsilon toxin causes excessive release of glutamate in the mouse hippocampus

Abstract: The mechanism of neurotoxicity of Clostridium perfringens epsilon toxin to the mouse brain was investigated. Intravenous injection in mice with the toxin caused seizure and excited hippocampal neurons. Microdialysis revealed that epsilon toxin induced excessive glutamate release in the hippocampus. Both the seizure and glutamate release were attenuated by prior injection with riluzole, an inhibitor of pre-synaptic glutamate release, suggesting that this toxin enhances glutamate efflux, leading to seizure and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Thus, this study also determined the toxicity of trypsin activated wild type Etx after intraperitoneal administration in groups of six mice. In previous studies trypsin activated Etx has been shown to have a LD 50 dose ranging from 70 ng/kg [20] to 320 ng/kg [10] when administered by the intravenous route to mice. There is less data on the LD 50 dose of wild type Etx when given by the intraperitoneal route to mice.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, this study also determined the toxicity of trypsin activated wild type Etx after intraperitoneal administration in groups of six mice. In previous studies trypsin activated Etx has been shown to have a LD 50 dose ranging from 70 ng/kg [20] to 320 ng/kg [10] when administered by the intravenous route to mice. There is less data on the LD 50 dose of wild type Etx when given by the intraperitoneal route to mice.…”
Section: Discussionmentioning
confidence: 96%
“…ETX toxin binds with high affinity to rat brain synaptosomes [111], and limited evidence suggests that the receptor might be a sialoglycoprotein [109, 111, 112]. The neurological disorders observed in several animal species seem to result from ETX action on hippocampus, leading to an excessive release of glutamate [108, 113, 114]. …”
Section: Epsilon Toxin (Etx)mentioning
confidence: 99%
“…It is produced by types B and D strains of the anaerobic bacterium Clostridium perfringens and primarily affects livestock in the form of rapidly fatal enterotoxemias, resulting in heavy economic losses [1]. The lethal effect of Etx has been associated with general edema and neurological alterations, leading to a glutamate-mediated excitotoxic effect and neuronal death [2], [3], [4], [5]. In addition, Etx also affects the renal system, producing congestion, interstitial hemorrhage and cytotoxicity of epithelial distal tubule cells [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%